Faith in the public square - Williams, Rowan, 1950-- (London : Bloomsbury, 2012)
This book contains critical commentary on contemporary issues by Rowan Williams, in his final book as Archbishop of Canterbury. Archbishop Rowan Williams is the most gifted Anglican priest of his generation. His views are consistent and orthodox and yet he has been consistently misunderstood - especially in relation to his views on contemporary society, public morality and the common good. In this, the final published work of his Archiepiscopate, Dr. Williams has assembled a series of chapters on matters of immediate public concern and the relationship of Christianity to these issues.
Introduction \ Part One: Secularism and its Discontents \ 1. Has Secularism Failed? \ 2. Secularism, Faith and Freedom \ 3. Convictions, Loyalties and the Secular State \ 4. Law, Power and Peace \ 5. Europe, Faith and Culture \ 6. Religion, Culture, Diversity and Tolerance \ 7. The Spiritual and the Religious \ Part Two: Liberalism, Pluralism and Law \ 8. Multiculturalism: Friend or Foe? \ 9. Faith and Enlightenment \ 10. Pluralism and the Public and Religious Spheres \ 11. Religious Hatred and Religious Offence \ 12. Religious Faith and Human Rights \ 13. Human Rights and Religious Faith \ Part Three: Living within Limits: The Environment \ 14. Changing the Myths We Live By \ 15. Renewing the Face of the Earth: Human Responsibility and the Environment \ 16. Climate Crisis: Fashioning a Christian Response \ Part Four: Housekeeping: The Economic Challenge \ 17. Ethics, Economics and Global Justice \ 18. Theology and Economics: Two Different Worlds? \ Part Five: Justice in Community \ 19. Sustainable Communities \ 20. The Gifts Reserved for Age: Perceptions of the Elderly \ 21. Criminal Justice \ 22. Big Society-Small World? \ Part Five: Religious Diversity and Civil Agreement \ 23. Analysing Atheism: Unbelief and the World of Faith \ 24. Religious Diversity and Social Unity \ 25. Faith Communities in a Civil Society \ Part Six: Rediscovering Religion \ 26. Religious Lives \ Acknowledgements \ Index
Includes bibliographical references and index.
Keywords: Church and social problems -- Anglican Communion; Church and social problems -- Great Britain; Great Britain -- Social conditions